Bilateral lower limb symmetry during sit-to-stand and stand-to-sit tasks in stroke patients with hemiplegia - Meijin Hou; Meijin Hou; Jian He; Dongwei Liu; Chenyi Guo; Ye Ma; Xiaobo Luo (Frontiers in Neurology)
IntroductionStroke patients with hemiplegia are at an increased risk of falling during sit-to-stand (Si-St) and stand-to-sit (St-Si) tasks, partly due to impaired bilateral lower limb symmetry. Maintaining symmetrical movement between the limbs in these tasks can help reduce fall incidence.MethodThis study aimed to investigate bilateral lower limb symmetry during Si-St and St-Si tasks in stroke patients with hemiplegia to compare their performance with healthy controls. Thirteen stroke patients and 13 healthy controls participated in the study. Participants were instructed to perform the 30-s chair stand test at their self-selected pace. Kinematic and kinetic parameters were calculated using OpenSim's inverse kinematics and inverse dynamics tools. Bilateral symmetry was quantified using the symmetry index (SI), with an asymmetry threshold set at 10%.ResultsThe stroke group exhibited significantly greater lower limb asymmetry in both kinematic and kinetic parameters during Si-St and St-Si tasks compared to the healthy controls, with the kinetic parameters being more pronounced. In the stroke group, notable bilateral asymmetry (SI > 10%) was observed in the ankle joint angle (P < 0.05) during both tasks. Furthermore, severe asymmetry (SI > 30%) was identified joint moments across all lower limb joints, vertical ground reaction forces, and medial-lateral center of pressure.DiscussionThese findings highlight the need for targeted rehabilitation programs focusing on improving strength, coordination, and balance. Close monitoring of SI values, particularly for kinetic parameters, is recommended to guide and evaluate the effectiveness of these interventions.